(R)‐12‐Hydroxystearic Acid Hydrazides as Very Efficient Gelators: Diffusion, Partial Thixotropy, and Self‐Healing in Self‐Standing Gels. Issue 23 (27th October 2016) - Li, Jingjing; Zhang, Mohan; Weiss, Richard G.
Abstract: The gelation properties of derivatives of N‐ alkylated ( R )‐12‐hydroxystearic acid hydrazide ( n ‐HSAH, n =0, 2, 6, 10; n is the length of an n‐ alkyl chain on the terminal nitrogen atom) in a wide variety of liquids is reported. The n ‐HSAH compounds were derived from a naturally occurring alkanoic acid, ( R )‐12‐hydroxystearic acid ( R ‐12HSA), and although they differ from the analogous N‐ alkyl ( R )‐12‐hydroxystearamides ( n ‐HSAA) only by the presence of one N−H group, their behavior as gelators is very different. For example, the parent molecule (0‐HSAH) is a supergelator in ethylene glycol, in which it forms self‐standing gels that are self‐healing, partially thixotropic, moldable, and load‐bearing; gels of 0‐HSAA are not self‐standing. 0‐HSAH is structurally the simplest molecular gelator of which we are aware that is capable of forming both self‐standing and partially thixotropic gels. Also, diffusion of the cationic dye erythrosine B and the anionic dye methylene blue in 0‐HSAH/ethylene glycol gel blocks is much slower than the self‐diffusion of ethylene glycol. Polarizing optical microscopy, X‐ray diffraction, and FTIR studies revealed that the self‐assembled fibrillar networks (SAFINs) of the gels are crystalline, and that 0‐HSAH molecules may be arranged in a triclinic subcell with bilayer stacking. The SAFINs are stabilized by strong hydrogen‐bonding interactions between the hydrazide groups of adjacent molecules and a perpendicular hydrogen‐bonding network between the pendent hydroxyl groups of 0‐HSAH. The other n ‐HSAH ( n =2, 6, 10) molecules appear to be arranged in orthorhombic subcells with monolayers and strong hydrogen‐bonding interactions between the hydrazide group of one gelator molecule and the hydroxyl group of a neighboring one. These results show how small structural modifications of structurally simple gelator molecules can be exploited to form gels with novel properties that can lead potentially to valuable applications, such as in drug delivery. Abstract : Starting to gel : The structure–gelation properties of a series of hydrazide derivatives of the naturally occurring molecule ( R )‐12‐hydroxystearic acid were studied. Among these, ( R )‐12‐hydroxystearic acid hydrazide is structurally the simplest gelator reported to date to form self‐standing, self‐healing, and partial thixotropic gels at very low concentrations.